AN ODORANT‐BINDING PROTEIN INVOLVED IN PERCEPTION OF HOST PLANT ODORANTS IN LOCUST Locusta migratoria. Issue 4 (10th February 2016) - Li, Jia; Zhang, Long; Wang, Xiaoqi
Abstract : Locusts, Locusta migratoria (Orthoptera: Acrididae), are extremely destructive agricultural pests, but very little is known of their molecular aspects of perception to host plant odorants including related odorant‐binding proteins (OBPs), though several OBPs have been identified in locust. To elucidate the function of LmigOBP1, the first OBP identified from locust, RNA interference was employed in this study to silence LmigOBP1, which was achieved by injection of dsRNA targeting LmigOBP1 into the hemolymph of male nymphs. Compared with LmigOBP1 normal nymphs, LmigOBP1 knockdown nymphs significantly decreased food (maize leaf, Zea mays) consumption and electro‐antennography responses to five maize leaf volatiles, ((Z)‐3‐hexenol, linalool, nonanal, decanal, and (Z)‐3‐hexenyl acetate). These suggest that LmigOBP1 is involved in perception of host plant odorants.